1970
DOI: 10.2464/jilm.20.240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu on impact strength of Al-Si alloys

Abstract: Effects of Cu on the impact strength and structures of Al-Si alloys were examined by mean s of Charpy impact test and metallographical method. The following three types of specimens were used: a) As cast. b) Solution heat treated at 500 °C for 240 min . for the above specimens. c) Artificially age hardened at 200 °C for 300 min. after the above solution heat treatment .(1) The impact strength of as cast alloys tended to be decreased with the increase in Si content and Cu addition. When Si content was low (appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The effects of iron on the mechanical properties of Al-Si casting alloys were investigated by Komastu et al 146 Their results show that iron has a detrimental effect on the impact strength of such alloys because of the formation of Al-Si-Fe compounds.…”
Section: Effects Of Additives On the Impact Propertiesmentioning
confidence: 99%
“…The effects of iron on the mechanical properties of Al-Si casting alloys were investigated by Komastu et al 146 Their results show that iron has a detrimental effect on the impact strength of such alloys because of the formation of Al-Si-Fe compounds.…”
Section: Effects Of Additives On the Impact Propertiesmentioning
confidence: 99%
“…14 Load-time relationship for $-notch and U-notch specimens. [65] The difference between the load-time curves for $-notch and U-notch specimens of Al-Si alloys, as observed in the work of Komatsu et a/., [65] is shown in Figure 2.14. The configuration of the $-notch specimens used in their study is shown in Figure 2 In view of the fact that unnotched samples were used in this study, higher impact energies were therefore expected to be obtained.…”
Section: Effect Of Sample Configurationmentioning
confidence: 57%
“…Komastu et al 252 Their results show that iron has a detrimental effect on the impact strength of these alloys because of the formation of Al-Si-Fe compounds. Table 5.2 shows the results for the different parameters as determined from the instrumented impact tests for the Sr-modified grain-refined RGM alloy, thus making it possible to investigate the effects of various additions of Fe, whether individually or in combination with Mn, in as-cast and heat-treated conditions, hi the as-cast condition, the total absorbed energy, E t , of the RGM alloy is found to decrease with an increase in Fe whether added individually, or in combination with Mn.…”
Section: Effects Of the Addition Of Fe And Mnmentioning
confidence: 99%